La Correspondance d'Erasme : Volume I: 1484-1514 - Erasmus, Desiderius, (European History and Culture - Book Archive pre-2000., 1967)
Published by the Institut Interuniversitaire pour l'Etude de la Renaissance et de l'Humanisme (Université Libre de Bruxelles & Vrije Universiteit Brussel). First integral translation of Erasmus' complete Correspondence in a modern language. Translated and annotated after the Latin standard edition, the Opus Epistolarum , edited by P.S. Allen, H.M. Allen and H.W. Garrod. Copious notes. The 12th and final volume is the General Index .